Hubungan Pengetahuan terhadap Swamedikasi Penyakit Gastritis pada Mahasiswa Kesehatan dan Non Kesehatan: Literatur Review - Shalena Tasya Rahmawati; Ihsanti Dwi Rahayu (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Introduction: Self-medication is an effort applied to treat symptoms and complaints of mild signs of disease. Gastritis or better known as ulcers is one of the disorders of the digestive tract caused by inflammation of the gastric mucosa and submucosa, which can be triggered by irritation and infection factors. Methods: This literature review was conducted by searching journal databases, including ScienceDirect, PubMed, and Google Scholar with the keyword "gastritis self-medication". Articles were selected based on inclusion and exclusion criteria. Results and Discussion: Based on the data reviewed, 62.3% of students reported having self-medicated gastritis correctly, but only 34.9% felt able to diagnose the disease correctly, and 65.1% admitted the potential for misdiagnosis. Higher knowledge was found in health students, as evidenced by the significant value of the relationship between knowledge and self-medication behavior. Conclusion: Several studies show that the success of self-medication increases with increasing knowledge, but the practice of rational drug use (including the selection of drug type, dosage, and time of use) has not been fully implemented, even by health faculty students.